Pelatihan Penentuan Harga Jual pada Usaha Budidaya Maggot di Kelurahan Kedung Cuwek, Kenjeran, Kota Surabaya - Arifin, Syamsul; Nuryadi, Nuryadi; Darim, Abu; Farida, Nur; Kurniawati, Kurniawati; Anisa, Nur; Isma'il, Mahmud (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Cultivating maggot is a business of cultivating organic waste materials. The maggot cultivation business is very promising for making profits, so it is necessary to pay attention to determining the right selling price. The purpose of community service is to provide training on how to determine the maggot selling price by calculating the cost of production and mark up. This method starts from planning with problem identification, conducting training on selling price determination and evaluation. The results and discussion of this community service activity are given training and hands-on practice on how to determine the selling price. This activity was also attended by maggot cultivation entrepreneurs. So that entrepreneurs can find out the benefits obtained independently.